TASERs and arrest-related deaths - Williams, Howard E. (Criminal justice (LFB Scholarly Publishing LLC), 2015)
Williams examines TASER use and high-risk group theory, which posits that people with certain physiological attributes, such as heart disease, mental illness, or drug use, are at increased risk of sudden death following application of a TASER electronic control device (ECD). Data derived from autopsy reports indicate few differences in the presence of such attributes between arrest-related sudden deaths following the application of an ECD and arrest-related sudden deaths that did not involve an ECD. The notable exception was deaths involving excited delirium, which appeared statistically more.